Perbandingan Perubahan Warna Resin Komposit Nanofiller dan Nanohybrid Setelah Perendaman Pada Susu Fermentasi - Irene Minardo Basaria Napitupulu; Mangatas HP Hutagalung (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2020)
This research was to determine the difference in the ratio of the color change of the nanofiller and nanohybrid composite resins after immersion in fermented milk. This study used nanofiller and nanohybrid composite resins in the form of tablets with a diameter of 10 mm and a thickness of 2 mm. 32 samples were divided into 2 groups, namely the nanofiller resin group and the nanohybrid resin group soaked in fermented milk for 7 days. The discoloration of nanofiller and nanohybrid composite resins was measured using a chromameter before and after immersion. The results of statistical analysis of the independent t-test showed that there was a difference between the color of the nanofiller resin and the nanohybrid, namely p = 0.015. The results of the analysis also showed a change in color between the nanofiller and nanohybrid composite resins before and after soaking the fermented milk for 7 days, namely p = 0.023 and p = 0.000. The conclusion of this study is that there are differences in the color change of nanofiller and nanohybrid composite resins in fermented milk immersion.